Long-Term Effects of Tea Consumption Habits on Cardiovascular Performance of Adolescent Population: An Observational Study of Adolescent Community in Jakarta, Indonesia - Laura Evangelia; Lontoh, Susy Olivia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Tea is a popular drink that is widely consumed in Indonesia. Some studies show the potential benefits of tea on cardiovascular health, but evidence regarding long-term effects in adolescents is limited. This study aims to evaluate the relationship between tea consumption habits and cardiovascular performance in the adolescent population in Jakarta. Methods: This prospective observational cohort study involved 1,500 adolescents aged 15-18 years in Jakarta. Data on tea consumption habits was collected through a structured questionnaire, while cardiovascular performance was measured through blood pressure tests, body mass index (BMI), and treadmill tests. Logistic regression and Cox proportional hazards analyzes were used to identify the association between habitual tea consumption and cardiovascular events over a 5-year period. Results: The results showed that regular tea consumption (≥3 cups/week) was associated with a reduced risk of hypertension (OR 0.65; 95% CI 0.48-0.88) and an increase in cardiovascular functional capacity as measured by treadmill testing (HR 0 .72; 95% CI 0.55-0.94). Conclusion: The habit of regular tea consumption among adolescents in Jakarta is associated with a reduced risk of hypertension and improved cardiovascular performance. Further research is needed to confirm these findings and explore the mechanisms underlying tea's protective effects.